Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Valorization of allelochemical-rich olive pomace: Comprehensive effect microbial nutrient release and ursolic acid-enhanced uptake improve crop growth and quality - Xisi Sun; Shuyang Wang; Fangzhu Guo; Junkai Wang; Guoqing Xiao; Qingfeng Wu; Yuhong Liu (Journal of Cleaner Production, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Texture-sweetness Co-design of dysphagia Foods:Research on the textural regulation and sweetener release mechanisms of soy protein gels by sucrose and xylitol - Yahui Du; Zengwang Guo; Chunfang Ma; Bolatkhan K. Zayadan; Qingfeng Ban; Hong Yang; Zhongjiang Wang; Hongbo Sun (Food Hydrocolloids, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Anammox enhanced anoxic/oxic/oxic/anoxic process for removing carbon, nitrogen, and phosphorus from extremely low carbon/nitrogen ratio wastewater: Feasibility, performance and mechanism - Qingfeng Cheng; Yutong Chen; Wenxing Zhao; Xujing Guo; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Bioresource Technology, 2026)

The impact of milling degrees on rice quality using simultaneous rheology and FTIR techniques: Focus on starch structure - Weijie Qi; Yaxing Xie; Hongyue Zhao; Jianjun Cheng; Qingfeng Ban; Mingruo Guo (Food Chemistry, 2025)

Focusing on the formation mechanism and foaming properties of casein-hyaluronic acid complexes: Manufacturing highly moldable 3D aerated foods - Yujie Lin; Haoyuan Geng; Zengwang Guo; Zhongjiang Wang; Qingfeng Ban; Ningzhe Wang (Food Hydrocolloids, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

A novel montmorillonite-based room temperature phosphorescence material by host-guest system - Yan Zou; Junjie Ding; Libing Liao; Qingfeng Guo; Pengfei Shuai (Applied Clay Science, 2025)

Numerical Study on the Influence of Catamaran Hull Arrangement and Demihull Angle on Calm Water Resistance - Sumin Guo; Xianhe Yang; Hongyu Li; Weizhuang Ma; Qunhong Tian; Qingfeng Ma; Xin Su; Zongsheng Wang (Journal of Marine Science and Engineering, 2025)
This study investigates the WAM-V (Wave Adaptive Modular Vessel) catamaran configuration, focusing on the hydrodynamic interaction between its articulated hulls. The unique hinged connection mechanism induces a relative angular displacement between the demihulls during operation, significantly modifying the calm water resistance characteristics. Such resistance variations critically influence both vessel maneuverability and the operational effectiveness of onboard acoustic detection systems. This study using computational fluid dynamics (CFD) technology, the effects of varying demihull spacing and the angles of the demihulls on resistance were calculated. Numerical simulations were performed using STAR-CCM+, employing the Reynolds-averaged Navier–Stokes equations (RANS) method combined with the k-epsilon turbulence model. The study investigates the free surface and double body viscous flow at different Froude numbers in the range of 0.3 to 0.75. The analysis focuses on the effects of the demihull spacing ratio (BS/LPP, Demihull spacing/Length between perpendiculars) on calm water resistance. Specifically, the resistance coefficient at BS/LPP = 0.2 is on average 14% higher than that at BS/LPP = 0.5. Additionally, the influence of demihull angles on resistance was simulated at BS/LPP = 0.42. The results indicate that inner demihull angles result in higher resistance compared to outer angles, with the maximum increase in resistance being approximately 9%, with specific outer angles effectively reducing resistance. This study provides a scientific basis for optimizing catamaran design and offers valuable insights for enhancing sailing performance.

Reduction of soybean globulin antigen by soybean protein isolate/γ-aminobutyric acid complexes: Effect of the different concentrations of γ-aminobutyric acid on the protein modification, antigen levels, and foaming properties - Zhishuang Xing; Jiayu Zhang; Fangxiao Lou; Zengwang Guo; Lianzhou Jiang; Qingfeng Ban; Zhongjiang Wang (Food Hydrocolloids, 2025)

The thermal stability of ·S2- and ·S3- radicals in afghanite - Yinghua Rao; Qingfeng Guo; Libing Liao (Mineralogy and Petrology, 2025)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Design and optimization of liquid nitrogen precooling BOG re-liquefaction process for LNG ships - Lesheng Liu; Ting Guo; Xianglei Kong; Jiubing Shen; Qingfeng Jiang; Yanyan Zhou; Xing Tong (International Journal of Refrigeration, 2024)

Enhancing carbon fixation and suppressing bacterial chemotaxis through carbon matrix nano-selenium to mitigate emissions of antibiotic resistance genes and virulence factors from chicken manure - Weikun Guan; Lizhi Li; Cheng Zhang; Dexian Zhang; Qingfeng Xing; Dongsheng Guo; Ouyang Hongbing; Haibo Zhang (Chemical Engineering Journal, 2024)

Potential of novel zinc-based nanomaterials on the microbial community, antibiotic resistance genes, and DNA replication in animal manure - Haibo Zhang; Lizhi Li; Gangfu Chen; Nancheng Yin; Jiangao Guo; Xinrui Ni; Yixin Liu; Ke Wu; Weikun Guan; Cheng Zhang; Xiaochun Wu; Shi Wenkai; et al. (Chemical Engineering Journal, 2024)

Charge compensators achieve controlled self-reduction of Europium in BaMgP2O7 - Hongling Wang; Ke Su; Bin Ma; Yujia Wang; Lefu Mei; Qingfeng Guo; Libing Liao (Chemical Engineering Journal, 2023)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Optimization and control strategy of BOG re-liquefaction process for LNG vessels - Ting Guo; Lesheng Liu; Jiubing Shen; Qingfeng Jiang; Sichen Wu; Yanyan Zhou; Yi Liu (International Journal of Refrigeration, 2023)

Predicting mobile users' next location using the semantically enriched geo-embedding model and the multilayer attention mechanism - Yao Yao; Zijin Guo; Chen Dou; Minghui Jia; Ye Hong; Qingfeng Guan; Peng Luo (Computers, Environment and Urban Systems, 2023)

Advanced synergetic nitrogen removal of municipal wastewater using oxidation products of refractory organic matters in secondary effluent by biogenic manganese oxides as carbon source - Qingfeng Cheng; Hui Tian; Xujing Guo; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Water Research, 2023)

Trade openness, globalization, and natural resources management: The moderating role of economic complexity in newly industrialized countries - Xiuping Guo; Xianglei Meng; Qingfeng Luan; Yanhua Wang (Resources Policy, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Characteristics and health risk assessment of heavy metal pollution in atmospheric particulate matter in different regions of the Yellow River Delta in China - Ting Liu; Changsheng Zhao; Qingfeng Chen; Luzhen Li; Guorui Si; Lei Li; Beibei Guo (Environmental Geochemistry and Health, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

2.5 V “water in salt” aqueous micro-supercapacitors based on polypyrrole-coated NiCo layered double hydroxides - Xijuan Li; Xukun Wang; Guo Liu; Xinyi Sui; Qingfeng Wu; Xinge Wang; Xueliang Lv; Erqing Xie; Zhengxing Zhang (Chemical Engineering Journal, 2023)

Hydrothermal variations in soils resulting from the freezing and thawing processes in the active layer of an alpine grassland in the Qilian Mountains, northeastern Tibetan Plateau - Qingfeng Wang; Qianqian Yang; Hong Guo; Xiongxin Xiao; Huijun Jin; Lili Li; Tingjun Zhang; Qingbai Wu (Theoretical and Applied Climatology, 2019)

Oxymatrine improves L-arginine-induced acute pancreatitis related intestinal injury via regulating AKT/NFkB and claudins signaling - Hui Zang; Zhiqiang Zhang; Qingfeng Liu; Huimin Xiao; Tian Sun; Enling Guo; Lankun Zhang; Bensong Gong (Medicinal Chemistry Research, 2019)

Primary limitation on vegetation productivity shifts from precipitation in dry years to nitrogen in wet years in a degraded arid steppe of Inner Mongolia, northern China - Lei Huang; Dangjun Wang; Luhua Yao; Xiaoting Li; Dengke Wang; Qingfeng Du; Yong Zhang; Xiangyang Hou; Yanjun Guo (Journal of Soils and Sediments, 2019)

Risk assessment of flood disaster and forewarning model at different spatial-temporal scales - Jun Zhao; Juliang Jin; Jinchao Xu; Qizhong Guo; Qingfeng Hang; Yaqian Chen (Theoretical and Applied Climatology, 2018)

Spatiotemporal variations in volume of closed lakes on the Tibetan Plateau and their climatic responses from 1976 to 2013 - Ruimin Yang; Liping Zhu; Junbo Wang; Jianting Ju; Qingfeng Ma; Falko Turner; Yun Guo (Climatic Change, 2017)

A new azaphilone from the entomopathogenic fungus Hypocrella sp. - Qingfeng Guo; Lili Dong; Xiangyun Zang; Zijian Gu; Xiaoyun He; Lindan Yao; Liping Cao; Junzhi Qiu; Xiong Guan (Natural Product Research, 2015)

Fluorescence and HPLC Detection of Hydroxyl Radical by a Rhodamine-Nitroxide Probe and its Application in Cell Imaging - Linying Cao; Qingfeng Wu; Qiang Li; Shijun Shao; Yong Guo (Journal of Fluorescence, 2014)

Multi-potentiality of a new immortalized epithelial stem cell line derived from human hair follicles - Cecilia Roh; Michael Roche; Zhiru Guo; Christos Photopoulos; Qingfeng Tao; Stephen Lyle (In Vitro Cellular & Developmental Biology - Animal, 2008)